Search your memory ! – an associative memory based desktop search system - Chen, Jidong; Guo, Hang; Wu, Wentao; Xie, Chunxin (Proceedings of the ACM SIGMOD International Conference on Management of Data (SIGMOD 2009), 2009)
We present XSearcher, an associative memory based desktop search system, which exploits associations by creating semantic links of personal desktop resources from explicit and implicit user activities. With these links, associations among memory fragments can be built or rebuilt in a user's brain during a search. The personalized ranking scheme uses these links together with a user's personal preferences to rank results by both relevance and importance. XSearcher enhances traditional keyword based search systems since it is closer to the way that human associative memory works.